IMPLEMENTASI PEMBELAJARAN BERDIFERENSIASI PADA MATA PELAJARAN IPS KELAS V SD NEGERI RAULO KABUPATEN GOWA - Ayu Islamiyah, Muliya; Idawati; Arifin, Jamaluddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to examine the implementation of differentiated instruction in Social Studies for fifth-grade students at SD Negeri Raulo, Gowa Regency, identify the supporting and inhibiting factors, and analyze students’ learning outcomes. This research employed a qualitative approach with a descriptive design and case study method. The research subjects consisted of a teacher and fifth-grade students. Data were collected through interviews, observations, and documentation, and analyzed using data reduction, data display, and conclusion drawing techniques. The results showed that differentiated instruction had been implemented through the adjustment of content, process, and product based on students’ characteristics, although it was not yet optimal. Supporting factors included teacher awareness and school support, while inhibiting factors included limited facilities and time constraints. The implementation had a positive impact on students’ engagement, motivation, and understanding.